METODE ISTINBAT HUKUM ZAKAT PROFESI PERSPEKTIF YUSUF AL-QARDAWI DAN IMPLIKASINYA TERHADAP PENGEMBANGAN OBJEK ZAKAT DI INDONESIA - Aziz, Muhammad; Sholikah, Sholikah (ULUL ALBAB Jurnal Studi Islam, 2015)
One object of charity which to this day is still debated Islamic jurist is zakat profession. There are many things that cause zakat profession are legally without a strong foundation in Islamic legal tradition, including; existence of zakat profession has never been practiced by the Prophet at the time he was still alive, it makes the existence of this zakat profession be considered ahistorical in Islamic law. Even NU, which is listed as a major Islamic organizations, have not decided the concept of zakat profession that has become the lifestyle of the upper middle-class Muslims in Indonesia. Other facts show that the practice of this profession charity raised in Indonesia after the emergence of Yusuf al-Qardlawi book entitled fiqh al-zakah, which is one of the points of study is obligatory zakat for Muslims profession. So the facts mentioned above, this study is important to do. Therefore, the wishes expressed in this study are; how the method istinbath charity law profession perspective of Yusuf al-Qardawi? And what are the implications of these ideas to the output object development of zakat in Indonesia? This study concluded that, the method used by Yusuf al-Qardawi in beristinbath to determine the basis of the profession zakat is obligatory for every Muslim is qiyas method, provided that: Maqis 'alaih it is charity gold and silver; ‘illat it is growing (al-nama'); legal obligation for the profession zakat worth with gold-silver or gold as mandatory alms-silver; and his charity far'u profession. While the implications arising from the results of istinbath method as mentioned above for object development of zakat in Indonesia is, that the object of zakat in Indonesia, which was originally based solely on the object based charity that conventional classical fiqh (gold-silver zakat, agricultural-crops, animals etc.), toward the object charity in the field of occupations and professions that grow and thrive in the modern era, such commissioners, advocates, public accountants etc.